1994
DOI: 10.1007/bf02088047
|View full text |Cite
|
Sign up to set email alerts
|

Histamine as an intermediate growth factor in genesis of gastric ECLomas associated with hypergastrinemia in mastomys

Abstract: Profound and sustained inhibition of gastric acid secretion has been associated with development of carcinoid tumors of the fundic enterochromaffin-like (ECL) cells in rodents. While ECL cell hyperplasia has been recognized in humans, the development of carcinoid tumors is rare and often confined to patients under treatment for gastrinoma related to the multiple endocrine neoplasia type I (MEN1) syndrome. The Mastomys was utilized as a model for the rapid induction of ECLomas by insurmountable acid secretory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Recent evidence has helped to clarify the function of HDC, histamine receptors and their possible involvement in cancer development. Histamine has been considered to be an important growth factor in colonic and gastric cancer as well as in melanoma [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has helped to clarify the function of HDC, histamine receptors and their possible involvement in cancer development. Histamine has been considered to be an important growth factor in colonic and gastric cancer as well as in melanoma [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of histamine in culture medium was performed by HPLC using precolumn derivatization with o-phthalaldehyde and 2-mercaptoethanol in borate buffer and fluorescence detection as previously described [12]. Samples of cell culture medium (400 Ìl) were extracted using Bond Elute columns prior to analysis.…”
Section: Assay Of Histaminementioning
confidence: 99%
“…The H 1 receptor is known to be involved in vasoconstriction 11 reported that both H 1 and H 2 receptors were expressed by G cells, and that gastrin secretion was inhibited by H 1 receptors and stimulated by H 2 receptors. Modlin et al 9 reported that histamine may also act as an autocrine growth factor for ECL hyperplasia via the H 1 receptor. Therefore, histamine may be an important regulator of all gastric endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Sandvik et al 8 reported that gastrin produced dose-dependent histamine release from ECL cells in the rat stomach. Modlin et al 9 reported that histamine H 1 receptors were expressed by ECL cells and that histamine was an autocrine growth factor for ECL cell proliferation. However, the mechanism by which histamine influences ECL cell proliferation is not still clear.…”
Section: Introductionmentioning
confidence: 98%